Factors Associated with Risky Sexual Behavior for Adolescents at Senior High School - Arisa Harfa Said Lubis; Anto Anto; Rusdiyah Rusdiyah (Utan Kayu Publishing, 2023)
Adolescents are a group at risk for health problems, one of which is sexual behavior. Sexual behavior is any behavior that is driven by sexual desire, both towards the opposite sex and the same sex. This study aims to analyze the factors related to risky sexual behavior for adolescents at SMA Negeri 5 Padangsidimpuan. This study was quantitative with a cross-sectional approach. The population and sample were all students in SMA Negeri 5 Padangsidimpuan with a total of 234 students using the proportional random sampling technique. The data was collected with a questionnaire and analyzed with the chi-square test and logistic regression. The results showed that gender (p=0.028), dating status (p=0.022), knowledge (p=0.000), attitude (p=0.001), parents’ role (p=0.002), peer influence (p=0.002), and information sources (p=0.004), there was an influence on sexual behavior in adolescents, while for age (p=0.456) it does not affect sexual behavior for adolescents. The most related variable was peer influence with a value of Epx. (B)=6,58558. Sexual behavior in adolescents is influenced by factors of Gender, Dating Status, Knowledge, Attitudes, Parents’ Role, Peers''s Influence, and Sources of Information. So need Education and counseling on reproductive health are important to reduce the problem in adolescents.